Enduring courage : ace pilot Eddie Rickenbacker and the dawn of the age of speed - Ross, John F., 1958- (St. Martin's Press, 2014)
The sensational true story of Eddie Rickenbacker, America's greatest flying ace, who above all the rest showed a nation the way forward in its quest for speed, endurance and courage.